Pore structure evolution and mechanism of plugging during dissolution-erosion of acid leaching minerals from uranium-bearing sandstone - Song, Jiayin; Sun, Bing; Cai, Qiue; Li, Junzhe; Li, Hao; Zeng, Sheng (Hydrometallurgy, 2025)
Mineral dissolution and erosion during the leaching of uranium-bearing sandstone have profound effects on the evolution of pore structure and uranium leaching rate. X-ray diffraction (XRD), scanning electron microscopy (SEM), and nuclear magnetic resonance (NMR) techniques were used to characterise mineral changes and pore structure evolution in samples. The results indicate that during the in situ leaching process, feldspar was transformed into clay minerals and quartz. Dolomite and calcite completely dissolved and formed a large amount of Ca2+, which increased the content of CaSO4. The CaSO4 and MgSiO3 precipitated particles formed in the reaction blocked the pores or migrated with the leaching solution, and the porosity of the sandstone initially decreased and then increased. Furthermore, the pores were divided into micropores, mesopores, and macropores, and combined with NMR fractal theory, it was found that the pore structure of sandstone exhibited multifractal characteristics. The obtained pore fractal dimension had a positive correlation with quartz, dolomite, calcite, and feldspar contents, whereas the other mineral components showed a negative correlation. This study provides a theoretical reference for understanding the mechanism of pore plugging and optimising the deplugging process in acid leaching for uranium extraction. •CaSO4 and MgSiO3 produced were the main precipitates that cause pore plugging.•The pore structure of uranium-bearing sandstone was complex during leaching.•The fluid forces led to changes in the pore structure of sandstone uranium ore.•The effect of different mineral components on pore structure was different.